(untitled) (World Science, 2021)
The article is devoted to a review of data on the prevalence and impact of cardiovascular diseases on the course and outcomes of the new coronavirus infection COVID-19. The review examines the relationship between COVID-19 and the functioning of the renin-angiotensin-aldosterone system, the pathophysiological mechanisms of their mutual influence. The analysis of the latest literature data on the safety of taking angiotensinconverting enzyme inhibitors and angiotensin II receptor blockers is presented. The causes and pathophysiological mechanisms of the development of acute myocardial damage in COVID-19 are discussed. The issue of organizing rehabilitation assistance for patients who have undergone COVID-19 is being considered. The main components and features of the COVID-19 rehabilitation program are presented.